Peran Guru Penggerak dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam - Dewi Yulianti, Ratna (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the role of Teacher Innovators (Guru Penggerak) in enhancing the quality of Islamic Religious Education (PAI) learning in elementary schools. Teacher Innovators function not only as educators but also as change agents who foster independent learning and the development of students’ character in accordance with local wisdom. This research employs a field study approach, with primary data sources including school principals, PAI Teacher Innovators, and students. Data were collected through observation, interviews, and documentation, while data validity was ensured using source triangulation, technique triangulation, and time triangulation. The findings indicate that the role of Teacher Innovators in improving PAI learning quality includes the innovation of teaching methods, increasing student engagement, utilizing educational technology, strengthening leadership and collaboration, and fostering student character. Key supporting factors are effective school management, teacher enthusiasm, and active student involvement, whereas inhibiting factors include limited time, technological constraints, differences in students’ comprehension levels, and varied parental support. These findings highlight the strategic role of Teacher Innovators in achieving optimal quality in Islamic Religious Education.